2022
DOI: 10.1007/s11033-021-07038-w
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DLGAP1-AS2 overexpression associates with gastric tumorigenesis: a promising diagnostic and therapeutic target

Abstract: Background: Aberrant expression of long noncoding RNAs (lncRNAs) is associated with the progression of human cancers, including gastric cancer (GC). The function of lncRNA DLGAP1-AS2, as an oncogene, has been identi ed in glioma, hepatocellular carcinoma, and cholangiocarcinoma but not in other malignancies. Therefore, this study was aimed to explore the association of DLGAP1-AS2 with gastric tumorigenesis and beyond.Methods and Results: The expression level of DLGAP1-AS2 was prevaluated in GC datasets from Ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Many studies have shown that lncRNAs have an important function in biology of cancers and are out of regulation in various cancers [11,25]. It has been shown that the expression of certain lncRNAs is involved in the development and progression of BC, highlighting the different expression patterns of lncRNAs in BC tissues compared to normal breast samples [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that lncRNAs have an important function in biology of cancers and are out of regulation in various cancers [11,25]. It has been shown that the expression of certain lncRNAs is involved in the development and progression of BC, highlighting the different expression patterns of lncRNAs in BC tissues compared to normal breast samples [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that lncRNAs participate in metastasis, tumorigenesis and progression of various cancers including BC. While some lncRNAs can act as tumor-enhancing agents, others provide a role as tumor inhibitors [9][10][11]. Some lncRNAs, such as MALAT1 and HOTAIR, are expressed through breast tumorigenesis, showing oncogenic properties; whereas others like GAS5 and XIST function as tumor suppressors [12].…”
Section: Introductionmentioning
confidence: 99%
“…ncRNAs play vital regulatory roles in developing and increasing tumorigenesis by interacting with different signaling pathways, and contain more than 80 % of the genomic content. The lack of interaction of ncRNAs with signaling networks may result in some diseases, such as cancer [ [48] , [49] , [50] , [51] ]. In addition, ncRNAs are able to induce [ 8 ] or inhibit tumorigenesis through the Hippo pathway in Refs.…”
Section: Non-coding Rnas and Their Function In The Hippo Pathwaymentioning
confidence: 99%